Association Between Irritable Bowel Syndrome and Risk of Parkinson's Disease: A Systematic Review and Meta-Analysis - Zhang, XinYue; Svn, Zhen; Liv, MengSi; Yang, Yan; Zeng, Rui; Huang, Qian; Sun, Qin (Frontiers in Neurology, 2021)
Background: Parkinson's disease (PD) and irritable bowel syndrome (IBS) are respectively one of the most common neurodegenerative diseases and functional bowel diseases in the world. Recent studies suggest that patients with IBS seem to have a higher risk of PD, which conflicts with the results of previous meta-analysis. Therefore, the purpose of this systematic review is to evaluate all available evidence, in order to clarify the association between PD and IBS. Methods: Two reviewers independently searched the PubMed, Embase, Web of Science, and the Cochrane library on April 25, 2021 to identify all records that explore the association between IBS and PD. All reports that clearly define PD and IBS and analyze the relationship between the two were included. The Newcastle-Ottawa scale was used to assess the risk of bias of included studies. Results: Five studies from four articles involving 2,044,110 subjects were included in this analysis. The pooled results demonstrated a significant association between PD and IBS (1.48; 95% CI: 1.35-1.62, P <0.001), with subtle heterogeneity (I2=0.0%, p=0.585). The association was observed across genders and increased with age. However, the available evidence cannot allow a reliable analysis of the causal relationship between IBS and PD. Conclusion: This study demonstrates a higher risk of PD among subjects with IBS. Future studies are required to further clarify the causation and underlying mechanism of the association.